Multimedia Design for Imelda Hospital Company Profile Indonesian Workers As Effective Promotional Media - Mamed Rofendi Manalu; Denni M Rajagukguk (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
Imelda Hospital for Indonesian workers is a hospital as one of the public service institutions that requires the existence of an accurate and reliable information system, and is sufficient to improve its services to the community and other related environments. To support the information and promotion media that are specifically intended only for Indonesian Workers' Imelda Hospital, in order to provide more detailed and in-depth information about services and facilities and information contained in the Indonesian Workers' Imelda Hospital, research on multimedia design, to solve the problem of how effective promotional media will be carried out to support the sustainability of Indonesian workers' Imelda hospitals.